Efficiency evaluation of cornea crosslinking in septic ulcers in small pets - Lukashina U.E.; Slesarenko N.A.; Shilkin A.G. (E3S Web of Conferences, 2021)
The article presents the morphological substantiation of the feasibility of using corneal collagen crosslinking, as well as comparative characteristics of standard therapeutic animal treatment with septic cornea ulcers and modified crosslinking. Methods of ophthalmological examination of small pets after modified crosslinking revealed the most favorable (in 91.2% of cases) recovery in comparison with the standard therapeutic technique, which is confirmed by keratomalacia inhibition, acceleration of corneal epithelization rate and reduction (by 40%) of rehabilitation period of the animal.